Le poème de la drogue - Rolland Caignard (Kaiak, 2019)
Many descriptive and prescriptive studies about the link between psychotropic and poetic writings have difficulty measuring the effects of the "psychedelic substances" and classifying the various poets who devote themselves to the artificial paradises. To simplify this research, while proposing a scholarly literary path that takes into account the questions of poeticity, we want to innovate by choosing, as thematic division, two moments of the creative process determined by taking drugs. Two overlapping phases of which we tried to describe the specificities. First, the moment of consumption, the flash (the shock), which brings us to a reflection on the abundance of hallucinated images, on the cry and falling asleep. Secondly, the post consumption, with the overdetermination of the "poem of drugs" (a concept from Riffaterre), its mimicry and its reflexivity. This chronological convenience aims at ordering precisely the testimonies of poets and poems related to them, and to ask the question of the production of poetic language related to these two moments, considering that the first moment of immediate consumption is not creative (in the sense of the legitimate classical work) and that only in a second moment the work is done. From Baudelaire or Gautier, to Burroughs, Danielle Collobert and Christophe Tarkos, to Henri Michaux, we have selected relevant texts that confirm these presuppositions.